A Movement Guidance System for the Blind Using a Fuzzy Logic Controller (Sebha University Conference Proceedings, 2024)
Safe and independent mobility is significant for blind persons due to the diverse nature of the surrounding environment. The fuzzy logic system has features that make it a suitable tool to address this problem and provide safe motor guidance through its fuzzy steering decisions, to avoid collisions with obstacles during mobility, this study aims to implement a fuzzy logic controller as a system to help blind persons' for movement guidance and prevent collisions with obstacles during movement. The system consists of three ultrasonic sensors as a guide to movement, mounted on a stick to guide the blind person. This system can provide a solution to help these people during their movement without the help of others, the system has been tested several times to ensure its accuracy and effectiveness, and the experimental results showed that, through result in the movement guidance and the fuzzy rules that were created to obstacles collision avoidance, the system can assist the person by guiding them as they navigate their environment and avoid collisions with obstacles.